Phospholipid synthesis fueled by lipid droplets drives the structural development of poliovirus replication organelles. - Ekaterina G Viktorova; Jules A Nchoutmboube; Lauren A Ford-Siltz; Ethan Iverson; George A Belov (PLoS Pathogens, 2018)
Rapid development of complex membranous replication structures is a hallmark of picornavirus infections. However, neither the mechanisms underlying such dramatic reorganization of the cellular membrane architecture, nor the specific role of these membranes in the viral life cycle are sufficiently understood. Here we demonstrate that the cellular enzyme CCTα, responsible for the rate-limiting step in phosphatidylcholine synthesis, translocates from the nuclei to the cytoplasm upon infection and associates with the replication membranes, resulting in the rerouting of lipid synthesis from predominantly neutral lipids to phospholipids. The bulk supply of long chain fatty acids necessary to support the activated phospholipid synthesis in infected cells is provided by the hydrolysis of neutral lipids stored in lipid droplets. Such activation of phospholipid synthesis drives the massive membrane remodeling in infected cells. We also show that complex membranous scaffold of replication organelles is not essential for viral RNA replication but is required for protection of virus propagation from the cellular anti-viral response, especially during multi-cycle replication conditions. Inhibition of infection-specific phospholipid synthesis provides a new paradigm for controlling infection not by suppressing viral replication but by making it more visible to the immune system.